a). [(-2)³ - 10 x (-5²) x (-30+50 : 2)] x (-50)=
=[(-8) - 10 x 25 x 10)] x (-50)=
=(-8 - 2500 ) x (-50)=
=(-8 - 2500 ) x (-50)=
=125400
b).(-3)² + 10 x [(-1)²⁰¹²+ 2 x (-2+2 x 3)]=
=9 + 10 x [1+ 2 x (-2+6)]=
=9 + 10 x (1+ 2 x 4)=
=9 + 10 x 9=
=9 + 90=
=99
c).(-2)¹⁹⁹ :2¹⁹⁷- 10 x {-2 -2 x [(-4⁷):2¹² -2]}=
=-(2²) - 10 x {-2 -2 x [(-2¹⁴):2¹² -2]}=
=-4 - 10 x [-2 -2 x (2² -2)]=
=-4 - 10 x (-2 -2 x 2)=
=-4 - 10 x (-6)=
=-4 + 60=
=56
d). 5 x {(-1)¹⁰⁰ + (- 41616 : 204 + (-1)¹⁰¹ x [-2 + 2 x (9-10)]}=
=5 x [1 + (- 204 -1 x 0)]=
=5 x (1 - 204 )=
=5 x ( - 203 )=
=1015